(untitled) (Research, Society and Development, 2021)
The first year of a child’s life is one of the periods of greatest susceptibility to the influence of protective or risk factors, which can affect adulthood. Thus, maternal responsiveness (MR) or the mother’s ability to detect the baby’s behavioral signs and respond to them, is a key component. In this sense, the objective was to comparatively analyze the maternal behavior and the outcome of child development of preterm infants born in a public and a private hospital during their first year of life. Twenty dyads attended the study, 12 from the Private Hospital (PrH) and 8 from the Public Hospital (PuH), being mothers of newborns < 36 6/7 weeks and with birth weight < 2.600 grams. The clinical and socioeconomic form, the Denver II Development Test (DENVER II) and the Social Interaction Scale (SIS) were used. Data were analyzed with the G-Test and p-value of 0.05. Among the mothers, 60% were aged between 30 and 39 years, of those who were graduates, 12.5% were from PuH and 58.4% from PrH, in relation to family income of 3 to 5 minimum wages, 37.5% were from PuH and 100% from PrH. The affect domain was significantly higher among the PrH dyads throughout the evaluation period in the SIS and in the DENVER II outcome. Therefore, it was shown that maternal interaction is essential for the behavior and skills of preterm infants, directly reflecting on growth and development, especially in their first year of life.